Internalisasi Nilai Pendidikan Karakter Pada Siswa Di MI Nur Riska Lubuklinggau - Muhamad Akip; Selamat; Indah Winarni; Mukhlas; Muhammad Hengki; Mutiara Salsabila (Edification Journal : Pendidikan Agama Islam, 2026)
This study aims to analyze the process of internalizing character education values among students at MI Nur Riska Lubuklinggau through Islamic school culture and religious habituation programs. This research employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation involving the principal, teachers, and students. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings indicate that the internalization of character education values is implemented through the integration of Islamic school culture, religious habituation, teacher role modeling, and communication books connecting school and family environments. The process reflects Thomas Lickona’s theory consisting of moral knowing, moral feeling, and moral action. Religious habituation activities such as congregational prayers, Qur’anic recitation, and the Smart and Motivation program contribute significantly to strengthening students’ discipline, honesty, responsibility, and social awareness. The study also reveals that communication books function as a medium of continuous character monitoring between teachers and parents. Supporting factors include strong Islamic school culture, teacher involvement, and parental participation, while challenges arise from digital media influence and differences in students’ family backgrounds. This study contributes to the development of Islamic character education through the integration of school culture, religious habituation, and family involvement in the digital era.